Short-term effects of cover crops on soil health and yield in established no-till systems - Crossman, Savanna (Kansas State University, 2019)
Agriculture in Kansas and the Great Plains faces many sustainability challenges. Cover cropping is a practice that can affect sustainability by improving soil health parameters in some environments, but more work is needed in the frame of no-till systems in eastern Kansas. Additionally, cash crop yield is an important consideration for production agriculture, but is only reported in less than one-third of soil health studies. Field experiments were conducted on long-term no-till (>10 years) farms in 2014-2017 near Burlington, Hutchinson, and Valley Falls, Kansas. Sites were selected in partnership with local extension, with typical cropping rotations for the area. The objectives of this study were to (i) determine the impact of cover crops on soil health (ii) quantify biomass of established cover crops (iii) quantify yield impacts of cover crops on cash crop yield by comparing single species cover crop (CS), multiple species cover crop (CM), and no cover crop (NC) treatments. In addition, a tillage (T) treatment was included at the Burlington site. Plots were arranged in a randomized complete block design with three replications. Analysis of the soil property data largely found no consistent treatment effects (alpha = 0.05), though sporadic differences were detected. For example, infiltration significantly differed among treatments at the Burlington site in fall 2016, where the T and NC plots had significantly higher rates than the CS and CM plots, but it did not repeat in the 2017 samplings. The Burlington location was the only site to have differences in soil aggregate properties. The aggregates in the tillage plots were getting smaller over time likely from the mechanical breakdown of annual tillage. A significantly smaller mean weight diameter was observed for T as opposed to the other treatments in spring 2016. In 2015 and 2016 the NC treatment also began to show higher proportions of the 0.25mm WSA and less 4.75mm and 2.00mm WSA than the cover crop plots. Very few significant differences were found in the soil biological or chemical parameters, and those that were found lacked repeatability across years. Significantly higher dissolved organic carbon concentrations were observed in the mixed cover crop treatment at the Burlington location for the fall 2017 sampling time, and pH had sporadic instances of significance as well. In conclusion, during the first three years of this project, cover crops have had minimal short-term effects on soil dynamic properties, or cash crop yield, in long-term no-till in eastern Kansas. These results imply that cover crops are likely not a hindrance nor an enhancement to grain corn or soybean yields in eastern Kansas. Additionally, there may be an opportunity for growers to reduce seed costs by planting a single species cover crop as there was no short-term yield or soil health benefit to planting a multi-species mix.
Keywords: Cover crops; Soil health; No-till; Yield